MHD Slip Flow and Heat Transfer on Stagnation Point of a Magnetite (Fe3O4 ) Ferrofluid towards a Stretching Sheet with Newtonian Heating - Mohamed, Muhammad Khairul Anuar; Ismail, Nurul Ainn; Hashim, Norhamizah; Mohd Shah, Norlianah; Salleh, Mohd Zuki (CFD Letters, 2021)
Present paper investigates the flow and heat transfer of Magnetite (Fe3O4) water based nanofluid termed as ferrofluid on stagnation point past a stretching sheet with slip effect. The methodology starts with transforming the non-linear partial differential equations that governed the model to ordinary differential equations, then solved numerically by Runge-Kutta-Fehlberg (RKF45) method in Maple software. The influenced and characteristics of pertinent parameters which are the stretching parameter, magnetic parameter, velocity slip parameter and solid volume fraction for nanofluid are analyzed and discussed. It was found that the magnetite (Fe3O4) ferrofluid provided higher wall temperature and heat transfer capabilities compared to water. Meanwhile, the presence of slip effect had minimized the skin friction coefficient.